Adoption of Internet Banking Services in India: An Empirical Study (Global Journal of Management and Business Research, 2017)
Understanding the adoption of a new technology is an essential process to determine its uses and future advancements. This study aims at investigating the adoption of such similar technology i.e., Internet Banking (IB). The study adapted the Technology Acceptance Model (TAM) and Perceived Web Security (PWS) construct to understand the adoption of IB services in India. Perceived Usefulness (PU) and Perceived Ease of Use (PEoU) are considered as the two main determinants to evaluate the Attitude towards Use (ATU) and Intention to Use (INTU) internet banking services. A well-designed questionnaire is used and 340 responses were collected to empirically test the hypothesized relations of the theoretical model developed. The relationship between the constructs are tested using Structural Equation Modelling. The extended model of TAM once again confirmed the role of PU and PEoU in affecting the attitude and intention to use IB services. All the hypothesis were significant except the effect of PWS on attitude towards use of IB services.
Keywords: technology acceptance model; internet banking; perceived web security; structural equation modelling